Transverse Myelitis and Guillain-Barré Syndrome Overlap Secondary to Bartonella henselae: Case Report - Jamir Pitton Rissardo; Ana Letícia Fornari Caprara (Prague Medical Report, 2019)
The GBS/ATM overlap is characterized by the simultaneous occurrence of Guillain-Barré syndrome (GBS) and acute transverse myelitis (ATM), which are two neurological autoimmune disorders. In this context, cat scratch disease (CSD) was rarely reported combined with this overlap. An adult female presenting fever, back pain, inferior limb weakness, and anuria was admitted to our hospital. On the physical exam, a distended bladder and bilateral lymphadenopathy were observed. The neurological assessment revealed muscle weakness, plantar flexion, and hyporeflexia in right with absence in left. Also, she reported hyperalgesia in inferior limbs. Her blood pressure was fluctuating being in the majority of the time hypertensive. A spinal cord MRI (magnetic resonance imaging) was suggestive of transverse myelitis. Methylprednisolone was started. The cerebrospinal fluid showed 37.0 cells/mm3 of white blood cell count, 49 mg/dl of glucose, and 50.7 mg/dl of protein. Ceftriaxone and vancomycin were started. On further questioning, the subject stated that her finger was bitten by a cat about two weeks before the beginning of the symptoms. Serological tests were positive for Bartonella henselae. Doxycycline and rifampin were started. After one-month, her symptoms improve but she continued with a radicular pain and weakness. An EMG (electroneuromyography) was suggestive of demyelination. IVIG (intravenous immunoglobulin) was started. After IVIG 4-day, the patient had recovery of her strength. To the authors’ knowledge, there are two case reports of pediatric individuals linking CSD and GBS/ATM. Still, this association in an adult patient has not been reported until the present moment.